Situation Awareness of Cough etiquettes of Hospital Security personnel and Janitors - Kusbaryanto, -; Listiowati, Ekorini (Bangladesh Journal of Medical Science, 2019)
Background: Nosocomial infection is a major problem in hospitals around the world. To minimize the risk of infection in hospitals and other healthcare facilities, cough etiquette has to be applied. Thus, good situation awareness and the understanding why cough etiquette is important are necessary. The purpose of this study was to find out the effective education on cough etiquette on hospital security personnel’s and janitors’ situation awareness on cough etiquette. Methodology: This research study followed quasy experimental design with pretest and post test control group design. The sampling technique was purposive sampling involving 24 respondents for experimental group and 27 respondents for the control group. The analysis of the data employed Wilcoxon test and it employed Mann Whitney test to find out the difference of independent variable medians. Questionnaires were used to gather data collection. Results: The result of the analysis presented a mean of 97,7 on the post-test of control group and a mean of 116,3 on the post-test of treatment group. Wilcoxon and Mann Whitney tests resulted p = 0,001 (< 0,05), which meant there were significant differences. Conclusion: Education on cough etiquette is effective to raise hospital security personnel and the janitors’ awareness on cough etiquette. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.814-817